The new international orientation towards a multipolar world: China and Russia as a model - Abdallah, Noura Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
This study deals with one of the important topics in the field of international relations, which shows the direction of the new forces towards the forming of a multipolar world and ending the unpopularity of the United States of America that dominates the international system. In the twenty-first century, the world, especially after the collapse of the Soviet Union, several changes that led to the emergence of competing powers in the United States of America, such as Russia and China. This study was prepared to show the path of that competition, which seeks, based on the political and economic changes that took place between the years (2011- 2023), to bring about a change in the international polarity and the existence of a different international pattern that is not controlled by a single force represented by the United States of America, but in which power and roles are distributed between new players from Russia and China and actors Non-states such as international organizations and economic blocs.